[BP.04.01] PLASMA MIR-LET7 EXPRESSION LEVEL IS POSITIVELY RELATED TO CAROTID INTIMA-MEDIA THICKNESS IN ESSENTIAL HYPERTENSION PATIENTS. (September 2017) - Huang, Y.; Chen, J.; Feng, Y.
Abstract : Objective: MicroRNAs (miR) play a critical role in the pathophysiology of arterial remodeling in essential hypertension, and are emerging as potential biomarkers and therapeutic targets in cardiovascular disease. The aim of this study was to assess the relationship of plasma miR-let7 expression level with subclinical atherosclerosis in untreated patients with newly diagnosed essential hypertension. Figure. No caption available. Design and method: We assessed the expression level of miR-let7 in atherosclerosis patients and age-sex matched healthy individuals. All patients underwent measurements of CIMT and ambulatory blood pressure (BP) monitoring. Plasma miR-let7 expression was quantified by real-time reverse transcription polymerase chain reaction. Correlations between miR-let7 expression and BP parameters and CIMT were assessed using the Spearman correlation coefficient and multiple linear regression analysis. Results: There were 240 participants including 60 healthy volunteers with normal carotid intima-media thickness (nCIMT), 60 healthy volunteers with increased CIMT (iCIMT), 60 hypertension patients with nCIMT and 60 hypertension patients with iCIMT. We observed the lowest miR-let7 expression (21.70 ± 1.45vs29.33 ± 2.58vs31.50 ± 1.80vs35.49 ± 2.33; P < 0.001) in healthy controls with nCIMT, followed by healthy controls with iCIMT, then hypertension patients with nCIMT and highest expression in hypertension patients with iCIMT. MiR-let7 was independently correlated with CIMT (r = 0.587, P < 0.001). Conclusions: Our findings present significant evidence that plasma miR-let7 represents a potential non-invasive atherosclerosis marker in essential hypertensive patients and provide new perspectives on the development of a new generation of biomarkers for the better monitoring of end-organ damage in hypertension.